Sleep Pattern Interference in the Cognitive Performance of Lusitano Horses - Barbosa, Ângela P.; Oliveira, Tiago M.; Trindade, Pedro Henrique E. [UNESP]; Seidel, Sarah R. T.; Tokawa, Paula K. A.; Jaramilo, Fernando M.; Roncati, Neimar V.; Baccarin, Raquel Y. A. (MDPI, 2024)
Like most mammalian, polyphasic sleep, equine sleep can be divided into two phases: the REM (rapid eye movement) phase and the NREM (non-rapid eye movement) phase. For this study, a randomized crossover experiment was conducted using ten purebred Lusitano horses, all dressage athletes aged from three to seven years old. The horses were filmed before the intervention to characterize their sleep patterns. REM sleep deprivation was achieved by not letting the horses attain sternal or lateral recumbency for three consecutive days, totaling 72 h. A spatial memory task and a visual attention test were performed. A recording time of 48 h appeared to be long enough to characterize the sleep patterns of the stalled horses. The total recumbency time of the studied population was lower than that previously reported in horses. Although the recumbency times before and after the intervention were similar, there was a tendency shown by the delta (p = 0.0839) towards an increased time needed to resolve spatial memory tasks in the sleep-deprived group. Future studies may deepen the understanding of horse sleep requirements and patterns, and the effects of environmental changes on horse sleep.
Keywords: learning; REM sleep; sleep–wake cycle; welfare